Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.35848/1347-4065/abebbd
|View full text |Cite
|
Sign up to set email alerts
|

Structural analysis of TaWN ternary alloy film applicable to Cu orientation control

Abstract: We examine a structure/texture of a thin TaWN film applicable to the Cu(111) orientation by using automated crystal orientation mapping in transmission electron microscopy. The 5 nm thick TaWN film with an fcc-TaN structure shows (111) orientation in spite of being extremely thin. This orientation of the TaWN film results in highly-oriented growth of Cu (111), and also contributes to the increase in Cu grain size. Such structural features have useful that effectively prevent an increase in the resistance of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…On the other hand, we proposed TaWN alloy films with the above two functions in our previous study, 14) and we demonstrated that the 5 nm thick TaWN alloy film is an excellent barrier in the Cu/ TaWN/Si system, which effectively suppresses Cu diffusion. [14][15][16] Furthermore, we demonstrated that a Cu film with a high orientation of Cu(111) on the TaWN/Si system can be obtained using only a 5 nm thick TaWN alloy film without the need for an underlying material for Cu orientation. 16) In ADMETA2022, we reported formation of the Cu film with Cu(111) orientation on the TaWN/SiO 2 /Si system using X-ray diffraction (XRD) and ω-rocking curve measurements.…”
mentioning
confidence: 84%
See 3 more Smart Citations
“…On the other hand, we proposed TaWN alloy films with the above two functions in our previous study, 14) and we demonstrated that the 5 nm thick TaWN alloy film is an excellent barrier in the Cu/ TaWN/Si system, which effectively suppresses Cu diffusion. [14][15][16] Furthermore, we demonstrated that a Cu film with a high orientation of Cu(111) on the TaWN/Si system can be obtained using only a 5 nm thick TaWN alloy film without the need for an underlying material for Cu orientation. 16) In ADMETA2022, we reported formation of the Cu film with Cu(111) orientation on the TaWN/SiO 2 /Si system using X-ray diffraction (XRD) and ω-rocking curve measurements.…”
mentioning
confidence: 84%
“…[14][15][16] Furthermore, we demonstrated that a Cu film with a high orientation of Cu(111) on the TaWN/Si system can be obtained using only a 5 nm thick TaWN alloy film without the need for an underlying material for Cu orientation. 16) In ADMETA2022, we reported formation of the Cu film with Cu(111) orientation on the TaWN/SiO 2 /Si system using X-ray diffraction (XRD) and ω-rocking curve measurements. 17) In this study, we investigate whether highly-(111) oriented and large-grained Cu films can be obtained on the TaWN/SiO 2 /Si system using a 5 nm thick TaWN alloy film.…”
mentioning
confidence: 84%
See 2 more Smart Citations